Dietary resources shape the adaptive changes of cyanide detoxification function in giant panda (Ailuropoda melanoleuca) - Huang, He (Sci Rep, 2016)
The functional adaptive changes in cyanide detoxification in giant panda appear to be response to dietary transition from typical carnivore to herbivorous bear. We tested the absorption of cyanide contained in bamboo/bamboo shoots with a feeding trial in 20 adult giant pandas. We determined total cyanide content in bamboo shoots and giant panda’s feces, levels of urinary thiocyanate and tissue rhodanese activity using color reactions with a spectrophotometer. Rhodanese expression in liver and kidney at transcription and translation levels were measured using real-time RT-PCR and immunohistochemistry, respectively. We compared differences of rhodanese activity and gene expressions among giant panda, rabbit (herbivore) and cat (carnivore), and between newborn and adult giant pandas. Bamboo shoots contained 3.2 mg/kg of cyanide and giant pandas absorbed more than 65% of cyanide. However, approximately 80% of absorbed cyanide was metabolized to less toxic thiocyanate that was discharged in urine. Rhodanese expression and activity in liver and kidney of giant panda were significantly higher than in cat, but lower than in rabbit (all P < 0.05). Levels in adult pandas were higher than that in newborn cub. Phylogenetic analysis of both nucleotide and amino acid sequences of the rhodanese gene supported a closer relationship of giant panda with carnivores than with herbivores.